Effect of thermal stress on the reproductive qualities of large white breed sows - Sergey N. Gudkov; Natalya N. Gorb; Olga A. Zajko; Ludmila P. Ermakova; Anton Intkhanukhak (Аграрная наука Евро-Северо-Востока)
The work is devoted to the study of reproductive qualities of sows subjected to heat stress after insemination during the period of insemination and before insemination (I, II and III groups, respectively). The breeding reproducer maintains a constant temperature in the range of 18.0...21.0 °C. Heat stress conditions (22.08±4.28…25.02±5.02 ℃) arose as a result of a malfunction in the air conditioning system in the premises of an industrial pig complex and lasted for six weeks. The greatest negative effect was observed in sows subjected to maximum heat stress during insemination (II group) – they had a decrease in fertility compared to the I group by 4.6 %, an increase in the number of underdeveloped piglets – by 2.5 and 6.1 % compared to the I and III groups, stillborns – by 4.3 and 4.1 %, respectively; the number of mummified piglets was also higher compared to the III group. In sows exposed to high temperatures before insemination (III group), there was an increase in underdeveloped piglets compared to the I group by 3.7 %. In sows inseminated before exposure to heat (I group), no negative consequences were found for their reproductive indicators.